2012
DOI: 10.3389/fonc.2012.00058
|View full text |Cite
|
Sign up to set email alerts
|

Radiation, Inflammation, and Immune Responses in Cancer

Abstract: Chronic inflammation has emerged as one of the hallmarks of cancer. Inflammation also plays a pivotal role in modulating radiation responsiveness of tumors. As discussed in this review, ionizing radiation (IR) leads to activation of several transcription factors modulating the expression of numerous mediators in tumor cells and cells of the microenvironment promoting cancer development. Novel therapeutic approaches thus aim to interfere with the activity or expression of these factors, either in single-agent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
130
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(134 citation statements)
references
References 235 publications
(235 reference statements)
2
130
0
2
Order By: Relevance
“…This pathway is a subtype of pattern recognition receptors responsible for primary recognition of pathogen and host-associated molecular patterns and the subsequent activation of type I IFN production that orchestrates an innate immune response (22)(23)(24). In addition to its role in inhibiting IFNβ expression, Suthar et al recently demonstrated that LGP2 governs CD8+ T-cell fitness and survival by inhibiting death-receptor signaling (25).…”
mentioning
confidence: 99%
“…This pathway is a subtype of pattern recognition receptors responsible for primary recognition of pathogen and host-associated molecular patterns and the subsequent activation of type I IFN production that orchestrates an innate immune response (22)(23)(24). In addition to its role in inhibiting IFNβ expression, Suthar et al recently demonstrated that LGP2 governs CD8+ T-cell fitness and survival by inhibiting death-receptor signaling (25).…”
mentioning
confidence: 99%
“…It is known that inflammation associated with mucositis can induce tumor promotion, activating premalignant lesions (36,44). It is one of the hallmarks of cancer, acting on any stage of tumorigenesis (45). Within this context, the fact that BNCT can be delivered without enhancing mucositis is not only an asset in terms of preventing toxicity but also in terms of inhibiting the development of novel tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Cytokines are thought to elicit augmented tumor surveillance, inhibit tumor growth, and have direct tumoricidal properties [18]. Thus, it is believable that neoadjuvant radiation to the large bulk tumor can activate robust antitumor specific immune responses, which is absent after postoperative RT to the tumor bed, according to recent studies focused to relation between radiation and immune system [19,20]. This synergy stems come from the fact that RT potentially converting the tumor into a patient-specific in situ vaccine capable of re-educating the immune system to recognize and reject cancer [21,22].…”
Section: Abscopal Effects Of Radiation Therapymentioning
confidence: 99%